Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/jsr.13766
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on interpersonal touch are related to subjective sleep quality

Abstract: Affective touch has been reported for its calming effects; however, it is less clear whether touch is associated with sleep. Here, the relationship between different touch variables and self-reported sleep indicators was investigated. Data were extracted from the Touch Test, a cross-sectional survey conducted in 2020. Data from a sample of 15,049 healthy adults from the UK (mean age = 56.13, SD = 13.8; 75.4% female) were analysed. Participants were asked to attribute positive, negative, or no effects on sleep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…This may be because one partner's snoring and unexpected sudden movements have been shown to disrupt the other partner's sleep (Troxel et al, 2007). Specifically with regard to affectionate touch, Dueren et al (2022) found that although most adults in their sample perceived that affectionate touch during co-sleeping would benefit their sleep, it was actually related to lower levels of subjective sleep quality, including increased reports of WASO. While evidence regarding associations between co-sleeping and health and well-being are mixed, we do know that people are actually less likely to report sleeping in the same bed as their partners as they get older (Lauderdale et al, 2014).…”
Section: Marital Quality and Insomnia Symptoms: Emotional Support And...mentioning
confidence: 96%
See 1 more Smart Citation
“…This may be because one partner's snoring and unexpected sudden movements have been shown to disrupt the other partner's sleep (Troxel et al, 2007). Specifically with regard to affectionate touch, Dueren et al (2022) found that although most adults in their sample perceived that affectionate touch during co-sleeping would benefit their sleep, it was actually related to lower levels of subjective sleep quality, including increased reports of WASO. While evidence regarding associations between co-sleeping and health and well-being are mixed, we do know that people are actually less likely to report sleeping in the same bed as their partners as they get older (Lauderdale et al, 2014).…”
Section: Marital Quality and Insomnia Symptoms: Emotional Support And...mentioning
confidence: 96%
“…Some research suggests that spousal touch while co-sleeping is associated with increased sleep quality (Shahid, 2017) and related outcomes, such as improved mood (Roberts et al, 2022). However, other research has found negative associations between touch while co-sleeping and sleep quality (Dueren et al, 2022). This may be because one partner's snoring and unexpected sudden movements have been shown to disrupt the other partner's sleep (Troxel et al, 2007).…”
Section: Marital Quality and Insomnia Symptoms: Emotional Support And...mentioning
confidence: 99%
“…Specifically, interpartner support-seeking behaviors may promote experiences of closeness and safety that lengthen patients' sleep duration, which has been shown to be lower than the recommended amount in patients with cancer (14,56). Supporting this perspective, studies have shown that intimate behaviors such as interpersonal touch (89,90) and handholding (91,92) are related to improved sleep quality and shorter nighttime awakening. Given the limited empirical evidence on dyadic associations between PTSS and sleep, future studies are warranted to test each of these speculations.…”
Section: Ptss Clusters Distinctly Associated With Various Sleep Markersmentioning
confidence: 99%
“…Düren et al (2023) report on an issue that has not been investigated too frequently in the past, i.e. interpersonal touch in relationship to subjective sleep quality.…”
mentioning
confidence: 99%
“…Though this is more of a "negative" result, I guess it can be considered very important for users of hormonal contraception. Düren et al (2023) report on an issue that has not been investigated too frequently in the past, i.e. interpersonal touch in relationship to subjective sleep quality.…”
mentioning
confidence: 99%